1970
DOI: 10.1073/pnas.67.3.1294
|View full text |Cite
|
Sign up to set email alerts
|

On Finitely Additive Vector Measures

Abstract: Abstract. In this paper we extend the well-known Vitali-Hahn-Saks and Nikod5rm theorems for measures to finitely additive vector-valued set functions.1. Introduction. In ref. 1, Brooks gave new proofs for the Vitali-HahnSaks'0'5'9 and NikodQm6 theorems for countably additive set functions. The main tool was the Schur theorem.2 By establishing a vector form of Phillips' theorem,7 which in turn generalizes Schur's theorem, we are able to extend the Nikodym theorem (Theorem 2) and the Vitali-Hahn-Saks theorem (Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
4

Year Published

1974
1974
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 1 publication
2
34
0
4
Order By: Relevance
“…The following proposition has been established by Brooks and Jewett [4] for sequences of finitely additive, strongly bounded vector measures on a a-algebra. The Brooks-Jewett arguments carry over to sequences of Rickart vector charges converging pointwise on a delta ring.…”
Section: Corollarymentioning
confidence: 99%
See 3 more Smart Citations
“…The following proposition has been established by Brooks and Jewett [4] for sequences of finitely additive, strongly bounded vector measures on a a-algebra. The Brooks-Jewett arguments carry over to sequences of Rickart vector charges converging pointwise on a delta ring.…”
Section: Corollarymentioning
confidence: 99%
“…The fundamental result is the Banach space formulation of Phillips' lemma [10], which Brooks and Jewett [4] have established.…”
Section: Corollarymentioning
confidence: 99%
See 2 more Smart Citations
“…As we indicated in Theorem 5.1, this example answers two other questions dealing with vector measures. In [9], using Rickart's notion of sboundedness, Brooks and Jewett showed that the pointwise limit of a sequence of s-bounded set functions was s-bounded. This result fails for representing measures.…”
Section: Y-imentioning
confidence: 99%